EVALUASI PEMILU SERENTAK 2019 DAN SISTEM PRESIDENSIAL - Efriza Efriza (Jurnal Renaissance, 2019)
This paper tries to explain the incompatibility of multiparty systems with presidential systems. The effectiveness of government policies with multiparty systems certainly complicates the assessment of political parties in the policy-making process. Overcoming the need for political support, the implementation of the 2019 Concurrent Election was approved as a solution, in which the simultaneous timing of presidential and legislative elections supported a positive relationship with the amount of presidential political support in the legislature. But in fact, the changes in the electoral system arrangement resulted in significant coattail effect, as well as the subsequent management of the government was still built based on a pragmatic functioning coalition.Keywords: Presidential System, Multiparty System, Coalition, Presidential Election, and Concurrent Election